2014
DOI: 10.1111/and.12392
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine and vitamin E - a promising pair in the combat against testicular oxidative stress in aged rats

Abstract: Oxidative stress is considered to play a key role in ageing. Carnosine alone or together with vitamin E may prove to be helpful in dealing with problems of ageing through its antioxidant activity. Testis, by producing steroids and possessing a poor antioxidant system may become a strong target for the chronic oxidative stress generated during ageing. Therefore we investigated the in vivo effect of carnosine alone or together with vitamin E on testicular oxidative stress in aged rats. In this study, young (5 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(71 reference statements)
2
6
0
Order By: Relevance
“…CAR is also found to improve JS with preserved spermatogenesis, which has also been observed in the study of Aydın et al. () in naturally aged rats. These results may clearly indicate the beneficial role of CAR on disrupted testicular function during ageing.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…CAR is also found to improve JS with preserved spermatogenesis, which has also been observed in the study of Aydın et al. () in naturally aged rats. These results may clearly indicate the beneficial role of CAR on disrupted testicular function during ageing.…”
Section: Discussionsupporting
confidence: 80%
“…Testicular dysfunction due to gamma‐radiation was shown to be restored by CAR through its anti‐apoptotic action (Haeri, Rajabi, Fazelipour, & Hosseinimehr, ). In a previous study, increased testicular TBARS and DC levels in naturally aged rats were found significantly decreased by CAR and CAR + Vit E treatments (Aydın et al., ). To our knowledge, the effect of CAR on testicular oxidative stress and glycation in GAL‐induced aged animals is not presented in the literature.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations